PENGARUH CEO OVERCONFIDENCE DAN INVESTOR INSTITUSIONAL TERHADAP RISIKO PERUSAHAAN - Ernawati Ernawati; Faisal Faisal (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of CEO overconfidence and institutional investors on company's risk. The population in this study were non-financial companies listed on the Indonesia Stock Exchange in 2016. Based on the sampling process, the total sample used in this study amounted to 263 companies. Data analysis was performed using SPSS 21 software. The analysis performed included descriptive analysis, classical assumption test, ordinary least square, and Moderated Regression Analysis. The results show that CEO overconfidence has not affect company's risk. Also, institutional investors, both active and passive, have not reduce company risk.